Trends in sulfate and organic aerosol mass in the Southeast U.S.: Impact on aerosol optical depth and radiative forcing. Issue 21 (11th November 2014) - Attwood, A. R.; Washenfelder, R. A.; Brock, C. A.; Hu, W.; Baumann, K.; Campuzano‐Jost, P.; Day, D. A.; Edgerton, E. S.; Murphy, D. M.; Palm, B. B.; McComiskey, A.; Wagner, N. L.; et al.
Abstract Emissions of SO2 in the United States have declined since the early 1990s, resulting in a decrease in aerosol sulfate mass in the Southeastern U.S. of −4.5(±0.9)% yr−1 between 1992 and 2013. Organic aerosol mass, the other major aerosol component in the Southeastern U.S., has decreased more slowly despite concurrent emission reductions in anthropogenic precursors. Summertime measurements in rural Alabama quantify the change in aerosol light extinction as a function of aerosol composition and relative humidity. Application of this relationship to composition data from 2001 to 2013 shows that a −1.1(±0.7)% yr−1 decrease in extinction can be attributed to decreasing aerosol water mass caused by the change in aerosol sulfate/organic ratio. Calculated reductions in extinction agree with regional trends in ground‐based and satellite‐derived aerosol optical depth. The diurnally averaged summertime surface radiative effect has changed by 8.0 W m−2, with 19% attributed to the decrease in aerosol water.